2014
DOI: 10.1039/c4ob00767k
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial synthesis of nicotine analogs using an Ugi 4-CR/cyclization-reduction strategy

Abstract: A practical one-pot synthesis of nicotine analogs from Ugi 4-CR/propargyl adducts is reported. This methodology allows the rapid construction of the pyrrolidine moiety present in nicotine through an intramolecular base-promoted 5-endo cycloisomerization process, followed by a reduction of the resulting mixture of 2- and 3-pyrrolines to afford nicotine analogs in good overall yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In an attempt to explain the formation of the 3-pyrroline 7a instead of the expected 2-pyrroline 8 , Vázquez and colleagues have proposed a mechanism for an analogous system, according to which the enolate would attack the terminal carbon of the alkyne . However, the base-induced isomerization of propargyl amides to allenamides is well documented, and, moreover, it is favored in our reaction conditions (Table , entries 4 and 5) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In an attempt to explain the formation of the 3-pyrroline 7a instead of the expected 2-pyrroline 8 , Vázquez and colleagues have proposed a mechanism for an analogous system, according to which the enolate would attack the terminal carbon of the alkyne . However, the base-induced isomerization of propargyl amides to allenamides is well documented, and, moreover, it is favored in our reaction conditions (Table , entries 4 and 5) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…in 2014 demonstrated a base‐mediated post‐Ugi cyclization strategy for the efficient construction of biologically relevant nicotine derivatives 35 in 40–84% yields (Scheme 11). [46] Mechanistically, the formation of dianionic intermediate 34‐A might be followed by two possible pathways: a) a 1,5‐H shift between the amide anion and proton of the methylene group leading to allenamide 34‐B , which then reacts intramolecularly to afford the 2‐pyrroline via 5‐ endo‐trig cycloisomerization, and b) an intramolecular attack of enolate group on the terminal sp‐C of the alkyne leading to dianionic intermediate 34‐C via 5‐ endo‐dig cycloisomerization, which after protonation afforded 3‐pyroline. Subsequent reduction of the resulting mixture of 2‐ and 3‐pyrrolines afforded nicotine analogs 35 in good yields.…”
Section: Base‐mediated Post‐ugi Transformationsmentioning
confidence: 99%
“…Vazquez et al in 2014 demonstrated a base-mediated post-Ugi cyclization strategy for the efficient construction of biologically relevant nicotine derivatives 35 in 40-84% yields (Scheme 11). [46] Mechanistically, the formation of dianionic intermediate 34-A might be followed by two possible pathways: a) a 1,5-H shift between the amide anion and proton of the methylene group leading to allenamide 34-B, which then reacts intramolecularly to afford the 2-pyrroline via 5-endo-trig cyclo- Shiri and coworkers demonstrated a base-mediated post-Ugi cyclization strategy to leading to biologically relevant γlactams 37 (Scheme 12). [47] Ugi adduct 36 derived from 2formylindole, (aliphatic/aromatic) amines, 3-chloropropanoic acid, and isocyanides underwent highly selective intramolecular cyclization to furnish a novel series of indolyl-based γbutyrolactams 37.…”
Section: Metal-free Base-mediated Post-ugi Transformationsmentioning
confidence: 99%
“…16 Under the Ugi protocol, a set of four components (an aldehyde, an amine, a carboxylic acid and an isocyanide) are assembled into a peptide-like adduct, with the release of a molecule of H 2 O. 19 With this precedent, and the fact that several syntheses of 5-substituted γ-lactams using the Ugi reaction are restricted, in most cases, to reagents with a tethered combination of an acid and a ketone/aldehyde, along with the other components usually employed in this transformation (Ugi-4C-3CR, Scheme 1B), 20,16b we envisioned the possibility of building the γ-lactam nuclei (cotinine and iso-cotinine analogs) by exploiting the reactivity of the peptidyl position of Ugi adducts bearing a 3-chloropropionic moiety (Scheme 1C). 17 Recently, we developed a synthetic protocol for the rapid access to nicotine analogs from Ugi-4CR through a 5-endo cycloisomerization-reduction process, where an intramolecular cyclization between an allenamide group 18 and an enolate generated in the peptidyl position is performed (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, we developed a synthetic protocol for the rapid access to nicotine analogs from Ugi-4CR through a 5-endo cycloisomerization-reduction process, where an intramolecular cyclization between an allenamide group 18 and an enolate generated in the peptidyl position is performed (Scheme 1A). 19 With this precedent, and the fact that several syntheses of 5-substituted γ-lactams using the Ugi reaction are restricted, in most cases, to reagents with a tethered combination of an acid and a ketone/aldehyde, along with the other components usually employed in this transformation (Ugi-4C-3CR, Scheme 1B), 20,16b we envisioned the possibility of building the γ-lactam nuclei (cotinine and iso-cotinine analogs) by exploiting the reactivity of the peptidyl position of Ugi adducts bearing a 3-chloropropionic moiety (Scheme 1C). Herein, we disclose the results of the synthetic strategy depicted in Scheme 1C.…”
Section: Introductionmentioning
confidence: 99%